A cis‐Divacant Octahedral and Mononuclear Iron(IV) Imide1. Issue 51 (19th October 2014) - Searles, Keith; Fortier, Skye; Khusniyarov, Marat M.; Carroll, Patrick J.; Sutter, Jörg; Meyer, Karsten; Mindiola, Daniel J.; Caulton, Kenneth G.
Abstract A rare, low‐spin FeIV imide complex [(pyrr2py)FeNAd] (pyrr2py2−=bis(pyrrolyl)pyridine; Ad=1‐adamantyl) confined to a cis‐divacant octahedral geometry, was prepared by reduction of N3Ad by the FeII precursor [(pyrr2py)Fe(OEt2)]. The imide complex is low‐spin with temperature‐independent paramagnetism. In comparison to an authentic FeIII complex, such as [(pyrr2py)FeCl], the pyrr2py2− ligand is virtually redox innocent.